Automating ICU emergency signaling - Bengali, Rashida; Yeazdani, Nabila; Zaman, Naima (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electronics and Communication Engineering, 2013.